Cyber-Physical System-Based Electronic Traffic Law Enforcement (ETLE) for Strengthening Public Security Governance in Indonesia - Adhitya Panji Anom; Adhisty Sitaresmi; Athifatul Wafirah (FAKULTAS DAKWAH UIN SALATIGA, 2025)
Electronic Traffic Law Enforcement (ETLE) represents a significant innovation in the digitalization of traffic law enforcement in Indonesia. This study aims to analyze the implementation of ETLE within the framework of Cyber-Physical Systems (CPS), examine its challenges and opportunities, and formulate governance-oriented policy recommendations. A descriptive qualitative approach was employed, using semi-structured interviews with 12 informants, including police officers, transportation experts, and road users. Legislative and comparative approaches were also adopted to assess the compatibility of ETLE with national regulations and to benchmark practices from Singapore, Japan, and South Korea. The findings reveal four key issues in ETLE implementation: infrastructure inequality, incomplete derivative regulations, uneven human resource capacity, and public resistance. The discussion highlights that while ETLE enhances transparency, accountability, and effectiveness, its sustainability depends on regulatory strengthening, infrastructure equity, officer capacity building, and community engagement. This study further proposes the integration of restorative justice principles as a participatory alternative in traffic law enforcement. Theoretically, it contributes to socio-legal studies by linking ETLE with CPS, while practically emphasizing governance reforms to ensure fairness, legitimacy, and sustainability.